A critical realist analysis of consent to surgery for children, human nature and dialectic: the pulse of freedom. Issue 2 (14th March 2020) - Alderson, Priscilla; Sutcliffe, Katy; Mendizabal, Rosa
ABSTRACT: Consent can only be voluntary, freely given and uncoerced. Can this legal adult standard also apply to children? High-risk surgery is seldom a wanted choice, but compared with the dangers of the untreated problem, surgery can become the least unwanted option. Critical realism helps to reveal explicit and hidden levels of informed and voluntary consent at empirical, actual and real levels, on the four planes of social being and through the four-stage dialectic. Instead of starting with the rational-legal adult patient standard of consent, and assessing how young children fail this, understanding of consent could start at the other end of life. What does innate physical-social-moral-intuitive human nature in the emotional embodied person tell us about the meaning and purpose of consent/refusal for self-preservation, for avoiding suffering and promoting wellbeing? This discussion paper considers examples of life-giving treatment for children, and ethical dilemmas including one of conjoined twins, when only one child could survive separation.